Toward sustainable crops: integrating vegetative (non-seed) lipid storage, carbon-nitrogen dynamics, and redox regulation - Winichayakul, Somrutai; Roberts, Nick (Frontiers in Plant Science, 2025)
The global challenges of climate change and rising energy demands necessitate innovative agricultural solutions. One promising strategy is the transformation of photosynthetic tissues into lipid-rich organs, providing energy-dense biomass for biofuel production while enhancing carbon sequestration. However, these metabolic shifts require substantial NADPH and ATP, reshaping cellular processes such as the Calvin-Benson cycle, glycolysis, and oxidative pentose phosphate pathways. This review explores the intricate metabolic and regulatory networks underpinning lipid accumulation, with a focus on carbon/nitrogen partitioning, redox regulation, and their implications for plant stress tolerance and productivity. Furthermore, we highlight recent progress in field applications, multi-omics integration, and emerging strategies to optimize lipid accumulation in crops while mitigating trade-offs in biomass yield and agronomic performance. Understanding these complex interactions will be essential for developing sustainable, high-lipid crops that support bioenergy production and climate-resilient agriculture.